Simultaneous Estimation and Validation of Ornidazole and Cefixime by HPTLC in Pure and Pharmaceutical Dosage Forms - SREEKANTH, N.; SHIVSHANKER, K.; SHANMUGA PANDIYAN, P.; ROOSEWELT, C.; SRINIVASA RAO, G.; GUNASEKARAN, V. (Asian Journal of Chemistry, 2010)
A simple, rapid, sensitive high performance thin layer chromatographic method has been developed and validated for simultaneous estimation of ornidazole and cefixime in pure and pharmaceutical dosage form. It was performed on TLC plate precoated with silica gel 60F254 as a stationary phase using mobile phase composing of methanol and water in the ratio of 60:40 v/v and the detection was carried out in absorbance/reflectance mode at 254 nm showing Rf value 0.95 for ornidazole and 1.15 for cefixime. The percentage estimation of labeled claims of ornidazole and cefixime from marketed tablet was found to be 99.06, 99.48 by height and 99.39, 99.51 by area, respectively. The method was validated in terms of accuracy, precision, specificity and ruggedness. Linearity was observed between 250 and 2500 μg/mL for ornidazole and 100 and 900 μg/mL for cefixime. The recoveries of drugs by standard addition method were found in the range of 98 and 98.4 for both the drugs. The proposed method is precise, accurate and can be used for routine analysis of ornidazole and cefixime tablet.